2014
DOI: 10.1016/j.nucengdes.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation-induced effects of proton irradiation on zirconium carbides with different stoichiometries

Abstract: Zirconium carbide (ZrC) is being considered for utilization in deep burn TRISO fuel particles for high-temperature, gas-cooled reactors. Zirconium carbide has a cubic B1 type crystal structure along with a very high melting point (3420°C), exceptional hardness and good thermal and electrical conductivities. Understanding the ZrC irradiation response is crucial for establishing ZrC as an alternative component in TRISO fuel. Until now, very few studies on irradiation effects on ZrC have been released and fundame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Examination after bulk proton irradiations at 800 • C to 0.7 and 1.5 dpa showed that both defect diameter and density increased with dose, matching the present results for that dose range [7]. Bulk proton irradiations performed at 800 • C [10], however, resulted in defect densities that were an order of magnitude lower and defect diameters that were twice as large for ZrC 0.9 than those found in the present study. A couple of differences between the two experiments may account for the differences in results.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Examination after bulk proton irradiations at 800 • C to 0.7 and 1.5 dpa showed that both defect diameter and density increased with dose, matching the present results for that dose range [7]. Bulk proton irradiations performed at 800 • C [10], however, resulted in defect densities that were an order of magnitude lower and defect diameters that were twice as large for ZrC 0.9 than those found in the present study. A couple of differences between the two experiments may account for the differences in results.…”
Section: Discussionsupporting
confidence: 86%
“…Some investigation into the effects of ZrC x stoichiometry on the irradiation response have been conducted using bulk proton irradiations at 800 • C to 1-3 dpa [10] and 1125 • C to 2 dpa [11]. However, there has been no systematic investigation into the effect of temperature on the accumulation of radiation damage in ZrC, and no irradiations have been performed at cryogenic temperatures where athermal reactions can be studied.…”
Section: Introductionmentioning
confidence: 99%
“…They noted that the sub-stoichiometric ZrC samples (C/Zr<1) had an improved irradiation resistant microstructure compered to hyper-stoichiometric ZrC samples (C/Zr>1). Huang et al [26] reported that ZrCx material after a proton irradiation at 800 °C was highly decorated with dislocation loops. The loop size and density depended both on dose and stoichiometry with ZrC 1.2 showing quite different behaviour compared to the lower C-ratio stoichiometries.…”
Section: Zrcmentioning
confidence: 99%
“…It was found that the dislocation loops transitioned from Frank to prismatic loops in ZrC at higher temperatures. Some investigations on the effects of stoichiometry on the irradiation response in ZrC x have been carried out using proton irradiations to 1–3 dpa at 800 °C [19] and 2 dpa 1125 °C [20]. In our previous study [21], we found that the superstructure modulation of the ordered carbon vacancies for Zr 2 C in ZrC 0.6 was destroyed under Au ion irradiation.…”
Section: Introductionmentioning
confidence: 99%